2010
DOI: 10.4103/1463-1741.64974
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of annoyance from low frequency noise under laboratory conditions

Abstract: The aim of the study was to investigate the annoyance of low frequency noise (LFN) at levels normally prevailing at workplaces in control rooms and office-like areas. Two different laboratory experiments were carried out. The first experiment included 55 young volunteers and the second one comprised 70 older volunteers, categorized in terms of sensitivity to noise. The subjects listened to noise samples with different spectra, including LFNs at sound pressure level (SPL) of 45-67 dBA, and evaluated annoyance u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 23 publications
4
22
0
Order By: Relevance
“…Persson and Bjorkman (1988) and Persson et al (1990) found that dB(A) underestimates the level of annoyance for low frequency noise. This, along with other related work implies that noise at low frequencies is considered more annoying by individuals (Broner, 1978;Berglund et al, 1996;Pawlaczyk-Luszczynska, 2010). Moreover, related research has also found that low frequency noise has a greater degree of 'unpleasantness' than noise in the A-weighted frequency bands (Inukai et al, 2000;Nakamura and Inukai, 1998).…”
Section: Introductionsupporting
confidence: 57%
“…Persson and Bjorkman (1988) and Persson et al (1990) found that dB(A) underestimates the level of annoyance for low frequency noise. This, along with other related work implies that noise at low frequencies is considered more annoying by individuals (Broner, 1978;Berglund et al, 1996;Pawlaczyk-Luszczynska, 2010). Moreover, related research has also found that low frequency noise has a greater degree of 'unpleasantness' than noise in the A-weighted frequency bands (Inukai et al, 2000;Nakamura and Inukai, 1998).…”
Section: Introductionsupporting
confidence: 57%
“…The most cited effects on human health refer to emotional changes, namely agitation, distraction, disappointment, stress, hypertension [7,[16][17][18] and the association of low-frequency noise with cognitive impairments [19], the development of cardiovascular diseases [20,21], disturbances in sleep and heart rate [22][23][24] and hypertension [25,26].…”
Section: Low-frequency Noise and Human Well-beingmentioning
confidence: 99%
“…Usually at these conditions the people complaints about insomnia, migraines, lack of concentration, or other, even more serious, health problems. [1][2][3]. The sound fields in rooms at low frequencies are complicated because of individual room modes.…”
Section: Introductionmentioning
confidence: 99%